PENGARUH PUPUK NPK DAN AIR KELAPA SEBAGAI ZAT PENGATUR TUMBUH ALAMITERHADAP PERTUMBUHAN BIBIT KAKAO (Theobroma cacao L.) DI MEDIUM SUB SOIL - Dodi Irvandi; Nurbaiti Nurbaiti (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The research aimed to see the interaction of NPK fertilizer and coconut water as natural ZPT, and the effect of NPK fertilizer, coconut water and to get the dose of NPK fertilizer and the best coconut water concentration on cocoa seed growth in the sub soil medium. The experiment was conducted in the experimental station of Agriculture Faculty of Riau University from June to August 2016. The research used Completely Randomized Design (RAL) consisting of 2 factors and 3 replications. The first factor of dose of NPK fertilizer was 0,2,4,6 g / plant, the second factor was coconut water 0%, 25%, 50%, 75%. Data have been statistically analyzed and examined further with BNJ if significant effect on level 5%. The outcomes indicated that there was interaction between NPK fertilizer and coconut water on cocoa seed height, leaf field and dry weight, simply did not interact on stem circumference, leaf number and root canopy ratio of cocoa seedlings. Giving a dose of NPK fertilizer 4 to 6 g / plant gives a better effect on cocoa seed height, stem circumference, leaf number, leaf area and dry weight of cocoa seedlings. Provision of 50% coconut water concentration gave a better effect on stem circumference, leaf number, leaf area and dry weight of cocoa seedlings. The dosage of NPK 6 g fertilizer and concentration of coconut water 50% showed the best treatment on cocoa seed height, leaf area and dry weight of cocoa seed in the sub soil medium. Keyword : Seedling, sub soil, NPK fertilizer, coconut water